2008
DOI: 10.3748/wjg.14.4949
|View full text |Cite
|
Sign up to set email alerts
|

Role of transforming growth factor-beta signaling pathway in pathogenesis of benign biliary stricture

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…In a previous study, high expression of TGF‐β1 was observed in the stenotic bile duct tissue of 23 patients (Geng et al . ).…”
Section: Discussionmentioning
confidence: 97%
“…In a previous study, high expression of TGF‐β1 was observed in the stenotic bile duct tissue of 23 patients (Geng et al . ).…”
Section: Discussionmentioning
confidence: 97%
“…We also observed a significant amount of fibrotic tissue deposition in the liver biopsies of BDI patients. In the literature, there is one report on increased Smad7 levels in tissue biopsies[ 36 ]. In this study, we were limited to analyzing only mRNA expression, and the expression of Smad7 and of ECM proteins need to be measured in BDI patients.…”
Section: Discussionmentioning
confidence: 99%
“…TGF‐β serves an important function in the pathogenesis of biliary strictures . In contrast to a rapidly ascending TNF‐α, the TGF‐β1 changed in a slower and longer duration.…”
Section: Resultsmentioning
confidence: 99%